Inequality and earnings dynamics in France: National policies and local consequences - Francis Kramarz; Elio Nimier-David; Thomas Delemotte (Quantitative Economics, 2022)
This paper provides new stylized facts about labor earnings inequality and dynamics in France for the period 1991-2016. Using linked employer-employee data, we show that (i) labor inequality in France is low compared to other developed countries and has been decreasing until the financial crisis of 2009 and increasing since then, (ii) women experienced high earnings growth, in particular at the bottom of the distribution, in contrast to the stability observed for men. Both result from a decrease in labor costs at the minimum wage and an increase in the hourly minimum in the aftermath of the 35h workweek policy, (iii) top earnings (top 5 and 1%) grew moderately while very top earnings (top 0.1 and 0.01%) experienced a much higher growth, (iv) inequality between and within cohorts follow the same U-shaped pattern as global inequality: it decreased before 2009 and then increased until 2016, (v) Individual earnings mobility is stable between 1991 and 2016, and very low at the top of the distribution, (vi) the distribution of earnings growth is negatively skewed, leptokurtic, and varies with age. Then, studying earnings dispersion both within and between territories, we document strong differences across cities as well as between urban and rural areas, even after controlling for observable characteristics. We also observe a continuous decrease in earnings inequality between territories. However, a larger inflation in rural territories mitigates this convergence. Finally, we document a strong reduction in inequality within rural and remote territories, again driven by changes at the bottom of the wage distribution.
Keywords: D31; E24; J31; J38; R00; 330; Earnings dynamics; top income inequality; mobility; geographic in-equality